Role of Intergroup Contact as Relational Initiative to Alleviate Prejudice among Faith Based Groups - Tauqeer Ahmed Lak; Prof. Dr. Ghulam Yasin; Mussarat Hussain (Journal of Management Practices, Humanities and Social Sciences, 2022)
Prejudice is defined as negative attitudes, feelings, or intentions toward other people based on the belief that they belong to different social groups. Prejudice influences young people's social experiences and contributes to intergroup conflicts and patterns of social exclusion throughout their lives. In this regard, the current study was conducted to see the effectiveness of intergroup contact in mitigating prejudice among university students and to examine the efficacy of intergroup contact in mitigating prejudice between outer-sect university students. Because of this, this study used a quantitative research design and survey research methods. The data was collected from students attending the three most prominent universities in the province of Punjab, which are situated in the province's south, north, and center, respectively. A questionnaire was used as a tool for data collection. Preexisting scales regarding variables were adapted and used in the study. The amended scale was provided to the students through email and the instant messaging application WhatsApp. The information was gathered from 218 respondents using a convenience sampling technique. Regression and correlation analyses were used in order to analyze respondents' inferential responses. The study results showed that there is a substantial and positive correlation between contact with outside sects and reduced prejudice towards those sects. Moreover, contact with out-group sects showed a positive and significant effect on attitudes toward prejudice reduction among university students. In the Pakistani context, there are many studies regarding prejudice, but research gaps exist. This study is trying to uncover the research gap of preexisting studies regarding prejudice. Our study focused on prejudice among faith-based groups; the area that was uncovered in this study is the role of Intergroup Contact as a Relational Initiative to Alleviate Prejudice among Faith-Based Groups.